Practices and Challenges of Good Governance Packages in Bule Hora Town Water Supply, West Guji Zone, Ethiopia - Abdisa Olkeba Jima (PanAfrican Journal of Governance and Development, 2023)
The issue of good governance has become a concern of scholars across the world. Developing countries like Ethiopia are affected by the challenges of good governance because of weak mitigation mechanisms. Specifically, the issues of water governance have gotten the attention of scholars recently. This research scrutinizes the Bule Hora town’s status of water and the practices and challenges of good governance in the water supply. The study employed both qualitative and quantitative methods. A researcher selected a sample of 99 participants from Bule Hora town households through a systematic random sampling technique. Findings show that the Bule Hora town's water coverage is 53.3%. The inefficiency of labor and ineffectiveness of the office to supply sufficient water challenge the town's water supply good governance. Moreover, the participation of the community in water governance could be higher besides problems of electric fluctuation, shortage of skilled workforce and manager rotation, financial constraints, and political interference in the water governance activity affecting the water provision of the town. It concluded that the level of effectiveness could be higher because Bule Hora town cannot supply pure water for residents with minimum cost, effort, and time. It recommends that the town diversify the water sources to increase the inhabitants' effective and efficient water supply. Further, the town needs to raise the participation of residents in water governance and activity.